The blind brain: How (lack of) vision shapes the morphological and functional architecture of the human brain. (November 2014) - Ricciardi, Emiliano; Handjaras, Giacomo; Pietrini, Pietro
Since the early days, how we represent the world around us has been a matter of philosophical speculation. Over the last few decades, modern neuroscience, and specifically the development of methodologies for the structural and the functional exploration of the brain have made it possible to investigate old questions with an innovative approach. In this brief review, we discuss the main findings from a series of brain anatomical and functional studies conducted in sighted and congenitally blind individuals by our's and others' laboratories. Historically, research on the 'blind brain' has focused mainly on the cross-modal plastic changes that follow sensory deprivation. More recently, a novel line of research has been developed to determine to what extent visual experience is truly required to achieve a representation of the surrounding environment. Overall, the results of these studies indicate that most of the brain fine morphological and functional architecture is programmed to develop and function independently from any visual experience. Distinct cortical areas are able to process information in a supramodal fashion, that is, independently from the sensory modality that carries that information to the brain. These observations strongly support the hypothesis of a modality-independent, i.e. more abstract, cortical organization, and may contribute to explain how congenitally blind individuals may interact efficiently with an external world that they have never seen.